Brasil indo-lusitano: influências culturais das Índias Orientais no Brasil Colonial - Maciel, Rodrigo Araújo (2012)
The present work focuses on the importance of the various natural and material contributions of the Portuguese overseas possessions located in Asia, such as Goa and Macao, in the formation process of colonial Brazil - inserted in a specific period of time that goes from 1672 to 1712. Here we sought to examine the portuguese royal measures that enabled and encouraged the transplantation of the Eastern biome wealthnesses to the Western side of the Lusitanian Empire - with emphasis in Bahia - and the social consequences of this policy in this specific period. Allied to this, we conducted an biblio-biographical analysis of the brazilian three races myth, relating its extensive use to certain historiographical gaps, such as that we intended to explore here.